Analysis of the Use of E-Commerce on Consumer Decisions in Buying Baby Food Products - Hadita Hadita; Wirawan Widjarnarko; Jumawan Jumawan; Christophorus Indra Wahyu Putra (Budapest International Research and Critics University, 2021)
This study aims to analyze the use of e-commerce on consumer decisions in buying baby food products. This research is quantitative. The object of this research is the consumer of Nindita – Happy baby porridge through the Grabfood application. The data collection technique used in this study was a questionnaire. This research was conducted by using the Non-Probability Sampling technique through Accidental Sampling with a sample size of 100 respondents. The results of the research on product quality and price have a positive and significant effect on purchasing decisions, both simultaneously and partially with statistical results using SPPS version 23. Hypothesis testing obtained t-count > t-table or (4,130 > 1,984) and Sig. 0.000 <0.05 Ho is rejected. Ha is accepted with a beta value of 0.242, which means that product quality has a positive and significant impact on purchasing decisions. Hypothesis testing obtained t-count > t-table or (6.338 > 1.984) and Sig. 0.000 <0.05 Ho is rejected. Ha is accepted with a beta value of 0.496, meaning that the price has a positive and significant effect on purchasing decisions. Hypothesis testing obtained F-count > F-table or (96.135 > 3.09) and Sig.0.000 > 0.05 with a beta value of 1.162 meaning that product quality and price have a positive and significant effect on purchasing decisions. Based on the results of the research that has been explained, it is concluded that partially product quality has a positive and significant effect on purchasing decisions for consumers of nindita baby porridge - happy through the Grabfood Application, the price partially has a positive and significant effect on purchasing decisions for nindita baby porridge – happy through the Grabfood Application, and simultaneously product quality and price have a positive and significant impact on the purchase decision of nindita baby porridge - happy through the Grabfood Application.